2019
DOI: 10.3892/ol.2019.10866
|View full text |Cite
|
Sign up to set email alerts
|

Four targeted genes for predicting the prognosis of colorectal cancer: A bioinformatics analysis case

Abstract: The molecular mechanisms underlying the development and progression of colorectal cancer (CRC) have not been clarified. The purpose of the present study was to identify key genes that may serve as novel therapeutic targets or prognostic predictors in patients with CRC using bioinformatics analysis. Four gene expression datasets were downloaded from the Gene Expression Omnibus database, which revealed 19 upregulated and 34 downregulated differentially expressed genes (DEGs). The downregulated DEGs were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…For example, it has been found that CXCL3 [28] and CXCL8 [40] participate in the pathogenesis of UC and can be used as therapeutic targets for UC. For CRA, a study by Mclean et al showed that the inflammatory cytokine genes CXCL1, CXCL2, CXCL3, CCL20, IL8 (CXCL8), CCL23, CCL19, CCL21, and CCL5are BioMed Research International 4) and CEACAM7 (carcinoembryonic antigen-related cell adhesion molecule 7) have been found to be associated with an unfavourable prognosis in CRC [41]. SLC4A4 was also found to be a differentially expressed gene common to UC and CRC [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that CXCL3 [28] and CXCL8 [40] participate in the pathogenesis of UC and can be used as therapeutic targets for UC. For CRA, a study by Mclean et al showed that the inflammatory cytokine genes CXCL1, CXCL2, CXCL3, CCL20, IL8 (CXCL8), CCL23, CCL19, CCL21, and CCL5are BioMed Research International 4) and CEACAM7 (carcinoembryonic antigen-related cell adhesion molecule 7) have been found to be associated with an unfavourable prognosis in CRC [41]. SLC4A4 was also found to be a differentially expressed gene common to UC and CRC [42].…”
Section: Discussionmentioning
confidence: 99%
“…APOA4 was reported to be closely related to urinary bladder cancer (Soukup et al, 2019). CYP3A4 is currently indicated for the treatment of ovarian and breast cancer (Fiszer-Maliszewska et al, 2018;Liu et al, 2019). Bian et al (2019) found that GCG affected the development and progression of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A4 is currently indicated for the treatment of ovarian and breast cancer (Fiszer-Maliszewska et al, 2018;Liu et al, 2019). Bian et al (2019) found that GCG affected the development and progression of colon cancer. Li et al (2019) demonstrated that XPNPEP2 was associated with lymph node metastasis in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulated gene expression of this gene may be inspected in the colon and rectal cancer [79,80]. CEACAM7 plays important role in cancer pathology and may provide valuable information to predict promising prognostic markers of CRC and to unravel the molecular mechanism of CRC [73,81,82].…”
Section: Discussionmentioning
confidence: 99%